Celebration of Saint Sava's Day in Serbian schools in the Salonica vilayet at the end of the 19th and beginning of the 20th century - Dedović, Vukasin (Norma, 2025)
Summary: This paper examines the celebrations of Saint Sava's Day in Serbian schools in the Salonica Vilayet at the end of the 19th and the beginning of the 20th century, as well as the impact of these celebrations on preserving tradition, raising national awareness, and maintaining the core spiritual values of the Serbian people in this region. The cultivation of national consciousness and keeping the tradition were the primary tasks of Serbian schools and churches in Old Serbia and Macedonia. In achieving these objectives, the celebration of Saint Sava’s Day in schools played a particularly significant role. Based on archival materials, reports from correspondents of Carigradski glasnik, and relevant literature, we attempt to describe the program and manner of celebrating this highly significant date in Serbian history. The reports indicate that the Saint Sava cult was exceptionally strong among the Serbian population in the Salonica Vilayet, as well as in the entirety of Old Serbia and Macedonia. Serbian consuls and national activists in Macedonia faced great challenges, as they encountered opposition not only from the Ottoman authorities but also from increasingly organized Bulgarian propaganda, operating through the Exarchate, and Greek propaganda, operating through the Patriarchate, both of which sought to suppress Serbian national-political and cultural-educational influence in the region. The pressure from all sides united the Serbs in their efforts to defend and preserve their customs. The celebrations of Saint Sava’s Day in the Salonica Vilayet took the form of quiet yet persistent resistance against all imposed hardships. In this context, the efforts of the Serbian people to honor this holiday with dignity should be understood.Keywords: Salonica, celebration, Saint Sava’s Day, Serbian schools, cake cutting, water blessing.
Keywords: Salonica; celebration; Saint Sava’s Day; Serbian schools; cake cutting; water blessing